EFECTO DEL SELENIO EN EL CULTIVO DEL PEPINO (Cucumis Sativus L.) BAJO CONDICIONES CONTROLADAS - Carrión Zambrano, Nathaly Maholy (2023)
Cucumber cultivation is of great economic and nutritional importance due to its high consumption rate, it serves as both fresh and industrialized food, the nutritional imbalances that a soil presents cause problems for the plant in its correct physiological functioning. It is necessary to focus studies on the implementation of selenium in crop fertilization as there is evidence of its health benefit.